Reconciling fiscal decentralization, environmental protection expenditures, and stringent regulations with the ecological priorities of the European Union - Satrovic, Elma; Somoye, Oluwatoyin Abidemi; Olaleye, Banji Rildwan; Lekunze, Joseph Nembo (Frontiers in Environmental Science, 2025)
This study elucidates how fiscal decentralization affects environmental sustainability, moderating the role of environmental policy stringency in the selected European Union (EU) countries between 1995 and 2020. In addition, economic upturn, import diversification, and environmental protection expenditures are utilized as control variables. The empirical findings of the Method of the Moments Quantile Regression (MMQR) disclosed that the environmental policy stringency and environmental protection expenditures help the EU achieve ecological priorities. In addition, import diversification also spurs environmental sustainability, with more substantial impacts on less energy and carbon–efficient nations. Furthermore, the MMQR outcomes divulged that fiscal decentralization (all indicators) endorsed the environmental deterioration of EU members, undermining the achievement of ecological urgencies. Nonetheless, via the means of environmental policy stringency, fiscal decentralization positively influences environmental sustainability. These findings unveil that the harmful impact of fiscal decentralization on environmental sustainability can be curtailed if EU members impose more stringent environmental policies. Herein, to fulfil the targets of Sustainable Development Goals (SDGs), in particular, SDG7 and SDG13, EU members should consolidate fiscal decentralization initiatives and environmental policy stringency to ensure the achievement of ecological priorities.